MANAJEMEN PEMBELAJARAN DI PONDOK PESANTREN KAMPUS AINUL YAQIN UNIVERSITAS ISLAM MALANG - Faridatul Isnaeni; Ach Faiso; Fita Mustafida (VICRATINA, 2020)
A problem that often occurs in Islamic boarding schools is the development of educational models for improving the quality of students and human resources. This problem can be caused by the institution has not implemented good management. Focus in this research is planning, implementation and evaluation or management of learning in Islamic boarding school Ainul Yaqin University of Islam Malang. This study used qualitative method and descriptive approach. Data collection is participant observation, semi-structured interviewers and documentations. The result of the study is the management of learning has already done well. Preparations before learning such as arranging subject matters, syllabus or learning unit (SAP) have written documentation already. Implementation of the learning process is done in the morning and night. Morning uses non-classical learning systems such as bandongan method especially for the Ma’had Aly and Isti’dad programs. The Tahfidh al-Qur’an program uses memorizing method. And the night uses the method of lectures, discussions, demonstrations and writing scientific papers. Assessment of learning outcomes uses summative evaluation, in the form of preliminary and final semester exams. The test method can be oral, written or practice.